Avaliação morfológica do consórcio de milho outonal irrigado com forrageiras tropicais - Pereira, Francisco Cézar Belchor Lages [UNESP]; De Mello, Luiz Malcolm Mano [UNESP]; Pariz, Cristiano Magalhães [UNESP]; De Mendonça, Veridiana Zocoler [UNESP]; Yano, Élcio Hiroyoshi [UNESP]; De Miranda, Elka Elice Vasco; Crusciol, Carlos Alexandre Costa [UNESP]; Martello, Jorge Martinelli [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2017)
Fall irrigated maize intercropped with tropical forages can raise the amount of crop residues and relative nitrogen yield and improve land use efficiency without decreasing grain yield. The aim was to evaluate the effect of modalities of fall-irrigated maize (Zea mays L.) intercropped with tropical forages on the components of production, grain, straw and relative nitrogen yield, competitive factors in the intercrop and land use efficiency, in no-till (NT) system in the lowland Brazilian Cerrado. A randomized complete block experimental design was used in a 4×3+1 factorial arrangement with one control treatment, constituting 13 treatments, with four replications (n=4). The treatments comprised four tropical forages intercropped with maize: palisade grass (Urochloa brizantha cv. Marandu), congo grass (Urochloa ruziziensis), and the guinea grass cultivars Tanzânia and Áries (Panicum maximum cv. Tanzânia and Áries); three intercropping modalities: forage sown simultaneously in the maize rows, mixed with fertilizer; forage sown (broadcast) on the same day as maize sowing; and forage sown, mixed with top-dressed fertilizer, at the V4 stage of maize; and one control treatment (maize monoculture). Regardless of the type of tropical forage and intercropping modality, intercropping exhibited minimum competition between crops and did not interfere on the yield components and grain yield of fall-irrigated maize. In addition, it increased the amount of straw, and improved land use efficiency and relative nitrogen yield in comparison to mono-cropped maize. The best options were congo grass sown simultaneously in the maize rows and guinea grass cv. Tanzânia and guinea grass cv. Áries sown broadcast on total area, as they raised the shoot dry matter of maize and forage and land equivalent ratio. Congo grass sown simultaneously in the maize rows also raised the relative nitrogen yield.
Morphological assessment of fall irrigated maize intercropped with tropical forages
Keywords: Lowland Brazilian Cerrado; Panicum; Urochloa; Zea Mays L